Raltitrexed plus oxaliplatin-based transarterial chemoembolization in patients with unresectable hepatocellular carcinoma. Issue 7 (August 2016) - Zhao, Chang; Fan, Liwei; Qi, Feng; Ou, Shengqiu; Yu, Lei; Yi, Xiaoyu; Ni, Bingqiang; Zheng, Zhiyong; Lu, Jianxun; Zhang, Chengwen; Chen, Changsheng; Lu, Xiong; et al.
Abstract : Raltitrexed has shown efficacy and safety in many tumor types; however, the clinical data on the treatment of hepatocellular carcinoma is rare. In this report, we aim to assess the efficacy and safety of raltitrexed plus oxaliplatin (OXA)-based transarterial chemoembolization (TACE) in patients with unresectable hepatocellular carcinoma (uHCC). Patients with uHCC were recruited from multi-centers in China and assigned randomly to raltitrexed+OXA-based ( n =76), fluorouracil+OXA-based ( n =76), and doxorubicin+OXA-based ( n =75) TACE treatment. The primary end point was overall survival (OS). Tumor response was assessed using response evaluation criteria in solid tumors (RECIST), modified response evaluation criteria in solid tumors (mRECIST), and European Association for the Study of the Liver criteria (EASL). Safety and toxicity were evaluated using the National Cancer Institute Common Toxicity Criteria. The raltitrexed group showed a better disease control rate evaluated using RECIST (raltitrexed vs. fluorouracil vs. doxorubicin: 96.1 vs. 84.2 vs. 86.7%, P =0.05) and a better overall response rate on the basis of mRECIST (67.1 vs. 47.4 vs. 50.7%, P =0.03) and EASL (67.1 vs. 47.4 vs. 49.3%, P =0.02). The median OS and median progression-free survival (PFS) were higher in the raltitrexed group (median OS: 13.4 vs. 9.6 vs. 8.5 months; median PFS: 6.7 vs 4.9 vs 4.6 months). The most common toxicities included elevated aspartate aminotransferase (78.9 vs. 86.8 vs. 81.3%) and abdominal nonspecific pain (68.4 vs. 81.6 vs. 78.7%). No significant differences were found in the overall number of patients who experienced any toxicity. Raltitrexed plus OXA-based TACE suggested a safe and efficacious regimen in uHCC patients. The results warrant further clinical investigation. Abstract : Supplemental Digital Content is available in the text.